2020
DOI: 10.26677/tr1010.2020.351
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye de Hayat ve Bireysel Emeklilik Şirketlerinin Finansal Performansının İncelenmesi

Abstract: The aim of this study is to examine the financial performance of life and pension companies which are the complementary to the state's social security system and part of social security reform in a period before the auto enrollment system. Within the scope of this study, life and pension companies, which are registered to the Pension Monitoring Center and whose data can be accessed as of the determined years, have been selected and their financial performance has been analyzed by TOPSIS method. As a result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Then, the MARCOS procedure is used to rank private pension and life insurance companies. As far as we know, unlike previous studies (Genç et al, 2015;Özbek, 2015;Ege et al, 2016;Şahin and Başarir, 2019;Noyan et al, 2019;Bayrakci and Aksoy, 2019;Acer et al, 2020;Uçar and Şahin, 2020), the financial performance analysis of life and pension companies is carried out within the framework of the SD-MARCOS model for the first time in this study. In other words, in spite of the fact that there are many studies in the previous literature focusing on financial performance analysis of life and pension companies in Turkey, no study using the SD-MARCOS performance evaluation model is found in the previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the MARCOS procedure is used to rank private pension and life insurance companies. As far as we know, unlike previous studies (Genç et al, 2015;Özbek, 2015;Ege et al, 2016;Şahin and Başarir, 2019;Noyan et al, 2019;Bayrakci and Aksoy, 2019;Acer et al, 2020;Uçar and Şahin, 2020), the financial performance analysis of life and pension companies is carried out within the framework of the SD-MARCOS model for the first time in this study. In other words, in spite of the fact that there are many studies in the previous literature focusing on financial performance analysis of life and pension companies in Turkey, no study using the SD-MARCOS performance evaluation model is found in the previous literature.…”
Section: Discussionmentioning
confidence: 99%